Palmitic Acid Methyl Ester Enhances Adipogenic Differentiation in Rat Adipose Tissue-Derived Mesenchymal Stem Cells through a G Protein-Coupled Receptor-Mediated Pathway - Jian-Hong Lin; Huan-Hsin Chang; Wen-Sen Lee; Pei-Ching Ting; Yu-Po Luo; Kun-Ta Yang (Stem Cells International)
Adipogenic differentiation from stem cells has become a research target due to the increasing interest in obesity. It has been indicated that adipocytes can secrete palmitic acid methyl ester (PAME), which is able to regulate stem cell proliferation. However, the effects of PAME on adipogenic differentiation in stem cell remain unclear. Here, we present that the adipogenic differentiation medium supplemented with PAME induced the differentiation of rat adipose tissue-derived mesenchymal stem cells (rAD-MSCs) into adipocyte. rAD-MSCs were treated with PAME for 12 days and then subjected to various analyses. The results from the present study show that PAME significantly increased the levels of adipogenic differentiation markers, PPARγ and Gpd1, and enhanced adipogenic differentiation in rAD-MSCs. Furthermore, the level of GPR40/120 protein increased during induction of adipocyte differentiation in rAD-MSCs. Cotreatment with PAME and a GPR40/120 antagonist together inhibited the PAME-enhanced adipogenic differentiation. Moreover, PAME significantly increased phosphorylation of extracellular signal-regulated kinases (ERK), but not AKT and mTOR. Cotreatment with PAME and a GPR40/120 antagonist together inhibited the PAME-enhanced ERK phosphorylation and adipogenic differentiation. PAME also increased the intracellular Ca2+ levels. Cotreatment with PAME and a Ca2+ chelator or a phospholipase C (PLC) inhibitor prevented the PAME-enhanced ERK phosphorylation and adipogenic differentiation. Our data suggest that PAME activated the GPR40/120/PLC-mediated pathway, which in turn increased the intracellular Ca2+ levels, thereby activating the ERK, and eventually enhanced adipogenic differentiation in rAD-MSCs. The findings from the present study might help get insight into the physiological roles and molecular mechanism of PAME in regulating stem cell differentiation.